2012
DOI: 10.1038/bjc.2012.221
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of urinary microRNA reveals a high sensitivity for bladder cancer

Abstract: Background:Urinary biomarkers are needed to improve the care and reduce the cost of managing bladder cancer. Current biomarkers struggle to identify both high and low-grade cancers due to differing molecular pathways. Changes in microRNA (miR) expression are seen in urothelial carcinogenesis in a phenotype-specific manner. We hypothesised that urinary miRs reflecting low- and high-grade pathways could detect bladder cancers and overcome differences in genetic events seen within the disease.Methods:We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 24 publications
2
91
1
1
Order By: Relevance
“…Reports on bladder cancer-specific miRNA signatures in urine samples are rare (12,15,16,(26)(27)(28). Using the RT-qPCR-based microarray we investigated the abundance of 754 different human miRNA species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports on bladder cancer-specific miRNA signatures in urine samples are rare (12,15,16,(26)(27)(28). Using the RT-qPCR-based microarray we investigated the abundance of 754 different human miRNA species.…”
Section: Discussionmentioning
confidence: 99%
“…In bladder cancer, urinary miR-126 was described as a specific indicator of BC (16), while overexpressed miR-96 and miR-183 were found to be correlated to tumour stage and grade (15). Another study showed a characteristic panel of 3 miRNAs (miR-15b/ miR-135b/miR-1224-3p) in urine sediments for detecting urothelial cell carcinomas (12).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, this study admitted missing 3% of invasive cancers using microRNAs (n=2). [32] Molecular markers as a predictor of tumor recurrence Using fluorescent-labeled DNA segments to detect chromosomal abnormalities associated with urothelial cancer is known as fluorescence in-situ hybridization (FISH). FISH has been shown to be 79% sensitive and 70% specific for diagnosing urothelial cancer.…”
Section: Main Body Molecular Markers As a Diagnostic Toolmentioning
confidence: 99%
“…BCa exhibits significant tumor heterogeneity, reflected by multiple genetic alterations and complex somatic mutational profiles [2]. New biomarkers, based on DNA methylation profiling [3], point mutations [4] and microRNAs [5], have been established in addition to many proposed protein biomarkers.…”
Section: Introductionmentioning
confidence: 99%